The Cambridge history of medieval canon law - Winroth, Anders 1965-; Wei, John C. (Cambridge New York Port Melbourne New Delhi Singapore Cambridge University Press, 2022)
Canon law touched nearly every aspect of medieval society, including many issues we now think of as purely secular. It regulated marriages, oaths, usury, sorcery, heresy, university life, penance, just war, court procedure, and Christian relations with religious minorities. Canon law also regulated the clergy and the Church, one of the most important institutions in the Middle Ages. This Cambridge History offers a comprehensive survey of canon law, both chronologically and thematically. Written by an international team of scholars, it explores, in non-technical language, how it operated in the daily life of people and in the great political events of the time. The volume demonstrates that medieval canon law holds a unique position in the legal history of Europe. Indeed, the influence of medieval canon law, which was at the forefront of introducing and defining concepts such as 'equity,' 'rationality,' 'office,' and 'positive law,' has been enormous, long-lasting, and remarkably diverse.
Keywords: Canon Law -- History -- Middle Ages, 600-1500; Law, Medieval; Canon Law -- Eastern churches -- History -- Middle Ages, 600-1500; Aufsatzsammlung